2015
DOI: 10.1097/md.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes and Increased Risk of Subsequent Asthma

Abstract: The association between type 1 diabetes mellitus (T1DM) and asthma remains controversial and has led to new interest in these 2 disorders. The purpose of this study was to examine the associations among young people with T1DM and asthma and offer a clinical demonstration of the balance between Th1 and Th2 responses.We conducted a retrospective cohort study by using data from the National Health Insurance (NHI) system of Taiwan. The cohort consisted of 3545 T1DM cases and 14,180 controls established during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 21 publications
7
39
0
Order By: Relevance
“…T1D and T2D have different pathogeneses and might affect CLRD outcomes distinctly or through different mechanisms. Some studies have reported a negative association between T1D and asthma, while others have reported increased risk of asthma and asthma exacerbations among subjects with T1D …”
Section: Discussionmentioning
confidence: 99%
“…T1D and T2D have different pathogeneses and might affect CLRD outcomes distinctly or through different mechanisms. Some studies have reported a negative association between T1D and asthma, while others have reported increased risk of asthma and asthma exacerbations among subjects with T1D …”
Section: Discussionmentioning
confidence: 99%
“…NOD mice are mainly used for type 1 diabetes (T1D) studies; however, the NOD genetic background predisposes to other autoimmune disorders, such as arthritis, sialitis, and thyroiditis . Human studies have shown that T1D patients have an increased incidence of allergy . However, little is known about how autoimmune genetic factors affect allergy.…”
Section: Introductionmentioning
confidence: 99%
“…12 Human studies have shown that T1D patients have an increased incidence of allergy. 13,14 However, little is known about how autoimmune genetic factors affect allergy. To investigate the interaction of autoimmune genetic factors with innate immunity in the CHS response, we studied CHS immune responses by using NOD mice deficient in innate immunity.…”
mentioning
confidence: 99%
“…In one study, it was shown that asthma symptoms preceded the diagnosis of diabetes by a few years, regardless of glucocorticoid treatment [24]. Likewise, uncontrolled diabetes has been associated with a higher risk of asthma, and poor glycemic control has been related to increased asthma risk [25]. In contrast, a large prospective study found no significant statistical relationship among women with asthma [26], suggesting that the diabetes-asthma association is still not sufficiently well established.…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been shown that diabetes is a pro-inflammatory state associated with airway inflammation [34]. Studies on type 2 diabetes have shown that it causes airway hyperresponsiveness in human airway smooth muscle cells in vitro [35], in diabetic animal models [36], and in humans [25]. Therefore, the most investigated pathway in the pathogenesis of the diabetes-asthma association is chronic inflammation such as RAGE.…”
Section: Mechanismsmentioning
confidence: 99%